Screening for asymptomatic bowel cancer in general practice. Issue 6410 (7th January 1984) - Lallemand, R C; Vakil, P A; Pearson, P; Box, V
Abstract : General practitioners screened 4284 asymptomatic people aged over 40 to compare the incidence of large bowel cancer and polyps with a control general practice (4288 patients). Compliance was best in young women (60%), and overall it was 42%. Twenty six patients who had a positive Haemoccult test result (1.5% of those screened) were examined by colonoscopy and 10 had polyps. The incidence of cancers in the two groups was similar but in the control (unscreened patients) practice no polyps were found.